Unintended Pregnancies Observed With Combined Use of the Levonorgestrel Contraceptive Implant and Efavirenz-based Antiretroviral Therapy: A Three-Arm Pharmacokinetic Evaluation Over 48 Weeks - Scarsi, Kimberly K.; Darin, Kristin M.; Nakalema, Shadia; Back, David J.; Byakika-Kibwika, Pauline; Else, Laura J.; Penchala, Sujan Dilly; Buzibye, Allan; Cohn, Susan E.; Merry, Concepta; Lamorde, Mohammed (Clinical Infectious Diseases, 2016)
Levonorgestrel subdermal implants are preferred contraceptives with an expected failure rate of <1% over 5 years. We assessed the effect of efavirenz- or nevirapine-based antiretroviral therapy (ART) coadministration on levonorgestrel pharmacokinetics. Methods. This nonrandomized, parallel group, pharmacokinetic evaluation was conducted in three groups of human immunodeficiency virus–infected Ugandan women: ART-naive (n = 17), efavirenz-based ART (n = 20), and nevirapine-based ART (n = 20). Levonorgestrel implants were inserted at baseline in all women. Blood was collected at 1, 4, 12, 24, 36, and 48 weeks. The primary endpoint was week 24 levonorgestrel concentrations, compared between the ART-naive group and each ART group by geometric mean ratio (GMR) with 90% confidence interval (CI). Secondary endpoints included week 48 levonorgestrel concentrations and unintended pregnancies.
Keywords: Contraceptive implant; Levonorgestrel; Efavirenz; Nevirapine; Unintended pregnancy